Sikap Petani terhadap Risiko Produksi Padi dan Faktor-Faktor yang Mempengaruhinya - Adreng Purwoto (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 1993)
Since the achievement of the Indonesia rice self sufficiency level in 1984, the trend of the wetland rice yield in Java has been declining. In this regard, attention has to be paid to turn the yield trend up by reducing the existing gap between the potential and the actual yields at the farm level. To a large extent, the government has been attempting to improve the actual rice yield as well as the total rice production through the establishment of various policies and programs which influence factors other than risk and uncertainty stemming from rice production. This study aims to measure the farmers attitude toward risks as well as as to examine the socio-economic factors which influence this attitude. This study was conducted in the rainfed rice producing region, of Grobogan District, Central Java. It was assumed that farmers in rainfed area face higher production risk than those in irrigated area. By applying the